The Ex utero intrapartum treatment (EXIT) procedure: case report of a multidisciplinary team approach: The Ex utero intrapartum treatment (EXIT) procedure - Sangaletti, Marina; Garzon, Simone; Raffaelli, Ricciarda; D’Alessandro, Roberto; Bosco, Mariachiara; Casarin, Jvan; Laganà, Antonio Simone; Sibona, Irene; Biban, Paolo; Franchi, Massimo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: The EXIT-to-airway procedure is aimed to provide the time required to secure airways when an extrinsic or intrinsic fetal mass raise concerns about airways control at delivery. Due to the rarity of the procedure, we aim to provide a summary of the appropriate prenatal planning by a multidisciplinary team. Methods: Report of a case of EXIT-to-airway procedure. Results: A 30 years-old woman, G2P1 with previous cesarean section, was referred to our Unit at 34 gestational weeks due to a fetal cervical mass of 7cm. An EXIT-to-airways procedure was performed by a multidisciplinary team after accurate preoperative planning and the practice simulations. The partial fetal extraction and the amnioinfusion of pre-heated saline were used to prevent fetal complications. The use of supplemental intravenous anesthesia with remifentanil and better control of uterine tone with nitroglycerin allowed to reduce the exposure to volatile halogen for both the mother and the fetus. The accurate preoperative planning and the practice simulations allowed us to perform the treatment safely in urgency due to the onset of spontaneous labor at 37 weeks and 6 days. Conclusions: The strong cooperation among specialists, accurate prenatal planning, and adopting all the required procedures and precautions are of paramount importance to successfully perform the EXIT-to-airway procedure.